2015
DOI: 10.1177/1071100715607006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Innovative Fixation System for Chevron Bunionectomy

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…In the patients with double osteotomy bunionectomy, we did not need to tighten the capsule as much as we did in the chevron bunionectomy alone group to obtain correction of the hallux valgus, which we reported on previously. 3 All patients in our group were either satisfied or satisfied with minor reservations. All patients reported that they would have the procedure done again if given the choice.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…In the patients with double osteotomy bunionectomy, we did not need to tighten the capsule as much as we did in the chevron bunionectomy alone group to obtain correction of the hallux valgus, which we reported on previously. 3 All patients in our group were either satisfied or satisfied with minor reservations. All patients reported that they would have the procedure done again if given the choice.…”
Section: Resultsmentioning
confidence: 86%
“…The ISO technique has been employed by us since 2011 for the correction and stabilization of mild to moderate hallux valgus with predictable outcomes. 3 Chevron osteotomy continues to be a reliable method for treating mild to moderate hallux valgus. [7][8][9]11 We continue to perform the ISO operative technique as outlined in the Operative Technique section; however, we elected to add the Akin proximal phalanx osteotomy to maintain and enhance correction, address minor rotational deformity, and obtain improved cosmesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an innovative intramedullary device was introduced for the fixation of the capital fragment in the distal metatarsal chevron osteotomy (4,5,15 The utilization of the metallic alloy implants could have been complicated with implant irritation and implant removal surgery may be warranted in some situations. In our study, the locking plate and the intramedullary device both had low profile feature.…”
Section: Discussionmentioning
confidence: 99%
“…28 This procedure was first described in 1981, and some modifications to this technique have been publicized, most recently adding focus on the fixation methods. 1-3 Numerous publications presenting the radiological outcomes and the clinical outcomes have been published. 5,18,20,27 One of the advantages of this method is its nature of a joint-preserving technique.…”
mentioning
confidence: 99%